Changing Grocery Shopping Behaviours Among Chinese Consumers At The Outset Of The COVID‐19 Outbreak - Li, Junxiong (Tijdschr Econ Soc Geogr, 2020)
This study focuses on the embryonic stages of the COVID‐19 pandemic in China, where most people affected opted to abide by the Chinese government’s national self‐quarantine campaign. This resulted in major disruptions to one of the most common market processes in retail: food retailing. The research adopts the theory of planned behaviour to provide early empirical insights into changes in consumer behaviour related to food purchases during the initial stages of the COVID‐19 outbreak in China. Data from the online survey carried out suggest that the outbreak triggered considerable levels of switching behaviours among customers, with farmers’ markets losing most of their customers, while local small independent retailers experienced the highest levels of resilience in terms of customer retention. This study suggests avenues for further scholarly research and policy making related to the impact this behaviour may be having around the world on society’s more vulnerable groups, particularly the elderly.